2010
DOI: 10.1097/eja.0b013e328335fbd1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of stroke volume variation compared with pleth variability index to predict fluid responsiveness in mechanically ventilated patients undergoing major surgery

Abstract: Although arterial pressure-derived SVV revealed the best correlation to volume-induced changes in SVI, the results of our study suggest that both variables, SVV and PVI, can serve as valid indicators of fluid responsiveness in mechanically ventilated patients undergoing major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 0 publications
5
90
0
1
Order By: Relevance
“…However, it was controversial whether SVV changed when IAP was increased in patients undergoing laparoscopic surgery (7,8). On the other hand, noninvasive plethysmographic variability index (PVI) is a new parameter used for the purpose of fluid responsiveness in patients receiving several kinds of surgeries (9)(10)(11)(12)(13)(14). In patients undergoing laparoscopic surgery, a previous study has suggested that PVI increased significantly after pneumoperitoneum was established (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was controversial whether SVV changed when IAP was increased in patients undergoing laparoscopic surgery (7,8). On the other hand, noninvasive plethysmographic variability index (PVI) is a new parameter used for the purpose of fluid responsiveness in patients receiving several kinds of surgeries (9)(10)(11)(12)(13)(14). In patients undergoing laparoscopic surgery, a previous study has suggested that PVI increased significantly after pneumoperitoneum was established (7).…”
Section: Introductionmentioning
confidence: 99%
“…We have asserted that SVV values must be estimated cautiously during pneumoperitoneum (6). Pleth variability index (PVI) is another dynamic index, and many studies concluded that it is useful for the assessment of fluid responsiveness in patients (2,(7)(8)(9) although one study concluded that PVI seems inaccurate to predict fluid responsiveness after conventional…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57][58] Solus-Biguenet et al, for instance, found a weak correlation of 0.29. 54 Nevertheless, despite this weak correlation, the majority of fluid responsiveness studies suggest that the respiratory variation in the PPG tracing is predictive of the hemodynamic response to fluid loading, [59][60][61][62][63] although this finding is not universal. 64,65 Surprisingly, despite the fact that the physiologic meaning of arterial respiratory variation has been understood for decades, extrapolation to the PPG waveform was completely missed by the manufacturers of pulse oximeters who considered this information ''noise'' and filtered it out through the application of high-pass filters.…”
Section: Fluid Responsivenessmentioning
confidence: 86%